Eternity by two. The Concept and Significance of Marriage in Søren Kierkegaard’s Discourse On the Occasion of a Wedding - Garrido Maturano, Ángel Enrique (Anales del Seminario de Historia de la Filosofía, 2024)
The article analyses the concept and significance of marriage in Søren Kierkegaard’s discourse On the Occasion of a Wedding from a pre-confessional hermeneutic-phenomenological perspective. First, it explains the meaning of falling in love, the resolution and the effective idea of ​​self and of God as the essential aspects of the concept of marriage. Then it reconstructs and articulates the aesthetic, ethical and religious significance inherent in a genuine marriage. Finally, from the categories of testimony and transcendence, it elucidates the sacred meaning of marriage as an experience of the spouses referred to the absolute through the interpellation to realise absolutely and unconditionally the love that unites them.